China's telecommunications revolution - Harwit, Eric, 1962- (Oxford : Oxford University Press, 2008)
A comprehensive look at China's telecommunications industry this text considers the way Chinese companies and the government acted in concert to put telephones and Internet access in the hands of hundreds of millions in less than 25 years, and looks at the consequences of this telecommunications 'revolution'.
Includes bibliographical references and index.
Description based on print version record.
Keywords: Telecommunication -- China; Telecommunication policy -- China; Telecommunication -- Economic aspects -- China; Telecommunication -- Social aspects -- China